The Preference for Wealth and Inequality: Towards a Piketty Theory of Wealth Inequality - Jean-Baptiste Michau; Yoshiyasu Ono; Matthias Schlegl (Center for Economic Studies and ifo Institute (CESifo), 2023)
What are the consequences of the preference for wealth for the accumulation of capital and for the dynamics of wealth inequality? Assuming that wealth per se is a luxury good, inequality tends to rise whenever the interest rate is larger than the economic growth rate. This induces the economy to converge towards an equilibrium with extreme wealth inequality, where the capital stock is equal to the golden rule level. Far from immiseration, this equilibrium results in high wages and in the golden rule level consumption for ordinary households. We then introduce shocks to the preference for wealth and show that progressive wealth taxation prevents wealth from being held by people with high saving rates. This permanently reduces the capital stock, which is detrimental to the welfare of future generation of workers. This also raises the interest rate, to the benefit of the property-owning upper-middle class. By contrast, a progressive consumption tax successfully and persistently redistributes welfare from the very rich to the poor.
Keywords: D31; E21; E22; H20; 330; capital accumulation; progressive wealth tax; wealth inequality; wealth preference